Youth in relation to agroecology: practices, promises, and perceptions in five countries - Rietveld, Anne; Guettou Djurfeldt, Nadia; Shijagurumayum, Meghajit; Gupta, Shweta; Tristán Febres, Maria Claudia; Chimonyo, Vimbayi Grace Petrova; Nehring, Ryan; Murugani, Vongai Gillian; Idoudi, Zied; Singh, Sonali (Taylor and Francis, 2026)
In the context of rising youth populations in many low- and middle-income countries, coupled with high youth unemployment and aging farmer populations, this paper asks in what ways agroecology, as a sustainable alternative to the conventional agricultural practices and paradigm, attracts youth to farming and rural-based livelihoods. We draw on empirical data from semi-structured interviews and photovoice conducted with young women and men in five countries: Kenya, India, Peru, Tunisia, and Zimbabwe. In our discussion, we highlight which dimensions and aspects of agroecology resonate with youth and why.